2004
DOI: 10.1249/01.mss.0000128143.93407.39
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training on ??1 ??2 ??3 Adrenergic and M2 Muscarinic Receptors in Rat Heart

Abstract: Our results show for the first time that in female rats an 8-wk treadmill training protocol alters specifically the left ventricle beta AR isoforms densities but not the M2 AchR one. These results could explain some of the beneficial cardiovascular adaptations of the physically trained heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 27 publications
6
35
0
1
Order By: Relevance
“…Barbier and colleagues also detected transcripts and cell surface expression of ␤ 3 -AR in rat hearts. They further found that LV ␤ 3 -AR density significantly increased in female rats with treadmill training for 8 weeks (Barbier et al, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…Barbier and colleagues also detected transcripts and cell surface expression of ␤ 3 -AR in rat hearts. They further found that LV ␤ 3 -AR density significantly increased in female rats with treadmill training for 8 weeks (Barbier et al, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…This eVect signiWes an important adaptation to training given that cardiac -adrenergic receptor density, as a whole, appears to decline with training. For example, swim training has been reported to down-regulate cardiac -adrenergic receptors without altering the ratio of 1 to 2s subtypes (Barbier et al 2004(Barbier et al , 2006Werle et al 1990). Conversely, a reduction in cardiac 1-adrenergic receptor density following training without an alteration in 2-adrenergic receptor density in female WKY rats has been shown (Barbier et al 2004(Barbier et al , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…In general, cardiac AR density has been shown to decline with exercise training without changing the ratio of AR1 to AR2s subtypes [96][97][98]. Still other studies have shown an attenuation of AR1s with training without altering AR2s.…”
Section: -Adrenergic Responsivenessmentioning
confidence: 95%